2008
DOI: 10.1292/jvms.70.1065
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of Gnotobiotic Piglets against Mycoplasma hyopneumoniae

Abstract: ABSTRACT. In this study, several cytokine responses were investigated during Mycoplasma hyopneumoniae (Mhp) infection using a gnotobiotic infection model. We found that several inflammatory cytokines (IL-1β, IL-8, IL-18, and TNF-α) and an anti-inflammatory cytokine IL-10 were induced from peripheral blood mononuclear cells (PBMC) of germ-free (GF) piglets stimulated with heat killed Mhp whole antigens, but no IFN-γ and IL-4 were induced by Mhp. After the intranasal infection of Mhp, IL-1β, IL-8, IL-18, and IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…High concentrations of IL-18 were found in rat lung homogenates by ELISA (Jordan et al, 2001) and both pro and mature IL-18 have been detected in human peripheral blood mononuclear cells (Puren et al, 1999). Low IL-18 concentrations in the BALF of un-infected 1-day-old gnotobiotic pigs had increased significantly by 2 and 4 weeks following infection with Mycoplasma hyopneumoniae (Muneta et al, 2008). Similar elevations were found 3 days PI in mice inoculated with herpes simplex virus type 1 (Reading et al, 2007) and human macrophages secrete IL-18 after inoculation with H3N2 influenza virus (Pirhonen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of IL-18 were found in rat lung homogenates by ELISA (Jordan et al, 2001) and both pro and mature IL-18 have been detected in human peripheral blood mononuclear cells (Puren et al, 1999). Low IL-18 concentrations in the BALF of un-infected 1-day-old gnotobiotic pigs had increased significantly by 2 and 4 weeks following infection with Mycoplasma hyopneumoniae (Muneta et al, 2008). Similar elevations were found 3 days PI in mice inoculated with herpes simplex virus type 1 (Reading et al, 2007) and human macrophages secrete IL-18 after inoculation with H3N2 influenza virus (Pirhonen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, previous studies have reported a higher IgG1 than IgG2 antibody response in pigs challenged with M . hyopneumoniae at local [36, 37] and systemic [36] levels. Although reasons for such inconsistencies are unknown, while in such previous studies IgG1 and IgG2 subclasses against P46 [37] or P97 [36] proteins were detected, in the present case, detected antibodies were directed to a recombinant M .…”
Section: Discussionmentioning
confidence: 99%
“…; Muneta et al . ). However, when co‐infected with the porcine reproductive and respiratory syndrome virus (PRRSV), the severity and duration of the pneumonia become worse (Thacker et al .…”
Section: Introductionmentioning
confidence: 97%